Isrāīliyyāt Discourse in Virtual Space: A Sociolinguistic Analysis of Gus Baha's Interpretation in Santri Gayeng YouTube Channel - Farahdiba, Ani Nabila; Alfarisi, Ahmad; Ibrahim, Aji Muhammad; Kamil, Ahmad Zaidanil (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2023)
This paper analyzes KH. Ahmad Bahauddin Nursalim's (Gus Baha') interpretation of Surah an-Naml verses 39-40 about the transfer of the throne of Queen Bilqis to the presence of Prophet Solomon a.s. This research is worth reviewing because there is a rejection of the interpretation by Gus Baha' in the Tafsir Jalālayn by Jalāluddīn al-Mahalli and Jalāluddīn al-Suyuṭi. This analytical descriptive study is derived from online media, namely the interpretation study by Gus Baha' published on the Santri Gayeng YouTube platform, making it a virtual ethnography.\. The author uses Labov and Waletzky's narrative structure analysis approach to explore Gus Baha's five interpretive structures, namely 1) Orientation, 2) Climax, 3) Evaluation, 4) Resolution, and 5) Coda. This study's results show that Gus Baha' rejects Jalaludin al-Suyuṭi's interpretation, which explains that Bilqis' throne emerged from under the chair. According to him, this does not make sense, which is isrāīliyyāt. Despite rejecting this interpretation, Gus Baha' gives his audience freedom regarding their belief in isrāīliyyāt. Gus Baha's rejection of isrāīliyyāt is based on his figure, who is a rationalist. This research also proves that the tradition of the cult of a tafsir essay that is quite phenomenal among pesantren is no longer done. Gus Baha' has succeeded in breaking the habit of pesantren in sacralizing a work of interpretation with his efforts to review the tradition of reading the book. The review was carried out by criticizing, reflecting, and understanding more deeply